Diagnostic utility of a line probe assay for multidrug resistant-TB in smear-negative pulmonary tuberculosis. - Binit Kumar Singh; Surendra K Sharma; Rohini Sharma; Vishnubhatla Sreenivas; Vithal P Myneedu; Mikashmi Kohli; Dinkar Bhasin; Sanjay Sarin (PLoS ONE, 2017)
To evaluate the performance of Genotype MTBDRplus VER 2.0 in the diagnosis of Mycobacterium tuberculosis (MTB) in sputum smear-negative pulmonary TB cases.A total of 572 Ziehl-Neelsen sputum smear-negative samples were selected and subjected to line probe assay (Genotype MTBDRplus VER 2.0), and culture in mycobacterial growth indicator tube (MGIT-960). Immunochromatographic test was used to confirm the MTB-complex (MTBC) in culture-positive samples and phenotypic drug-susceptibility testing was done using MGIT-960.The line probe assay was able to diagnose MTBC in 38.2% (213/558) of specimens after excluding 14 nontuberculous mycobacteria. Sensitivity and specificity of the assay were 68.4% and 89.3% respectively, considering MGIT-960 culture as gold standard after excluding contaminated and invalid results. On comparing with composite reference standard, the assay had 71.5% sensitivity and 100% specificity in the diagnosis of tuberculosis. The sensitivity and specificity for detecting resistance to rifampicin (RMP) were 100% and 99.24% respectively and for resistance to isoniazid (INH) were 97.62% and 98.55%, respectively.Genotype MTBDRplus VER 2.0 is a rapid and precise diagnostic tool for detection of MTB in sputum smear-negative samples. It also facilitates accurate diagnosis of RMP and INH resistance within turn around-time.